Accuracy of the APLS formula, the APLS normal range method and the broselow paediatric tape in estimating the body weight of Malaysian children - Wil, Fairuz Ramadanu Che (2018)
Background: Rapid establishment of children body weight is crucial for resuscitation as it enables calculation of drug doses, amount of fluid to be administered, and amount of energy to be applied. Actual weight is impractical to measure in a critically ill child. This study aims to compare the accuracy of Advanced Paediatric Life Support (APLS) formula, APLS normal range table and the Broselow Paediatric Tape. Methods: Participant were selected from children from one to five point nine years old attending the Accident and Emergency department and Paediatric follow up clinic in Hospital University Sains Malaysia, Kelantan, and Paediatric and general clinics in Institut Perubatan dan Pergigian Termaju, Penang. Demographic characteristics were obtained. Weight and height of each child were measured using a calibrated scale and measuring tape. Estimated weights were later determined by using the APLS formula, the APLS table and the Broselow tape. The primary outcome was the accuracy within 10% of the measured weight. Results: The number of children included in this study were 464. There were 239(51.5%) boys and 225(48.5%) girls. All three methods overestimated the weight of the children with the APLS formula overestimating 64.9%, the APLS table 61.4% and the Broselow tape62% of them. However, the Broselow tape is the most accurate tool with 33% of the estimation within 10% of the actual weight, followed by the APLS table (29.5%) and the APLS formula (26.5%). The Broselow tape overestimated the weight with a mean difference of 14.79%(95% limits of agreement 47.1 to -17.5), the APLS table with 15.32%(95% limits of agreement 54.8 to -24.2) and the APLS formula with 17.48%(95% limits of agreement 59.4 to -24.4). Conclusions: The three methods consistently overestimated the weight. The Broselow tape appeared to be the most accurate out of them. The more recent APLS group recommendation, APLS table is more accurate than the APLS formula.